Slogan “Peganglah Atau Kembalilah Kepada al-Qur’an Dan al-Sunnah [Q&S]” Isu Dan Tantangan Kepada Dakwah Islam: Analisis Dari Persepektif Pemikiran Islam - WZ Kamaruddin Wan Ali; Fifi Hasmawati (Wardah, 2019)
Abstract: The slogan plays an important role in the process of captivating the mad‘u in the context of Islamic preaching. The selection of slogansneeds to do through a specific process to allow them to be disseminated to the Muslim public. A good, effective slogan (tagline) will fulfilthe goals and vice versa. The slogan “Hold or Return to the Qur'an and the Sunnah (Q&S),” popularly known by the religious scholars, representing any individual or organization must be demonstrated in theory and practice, ideal and reality, outward and inward. Issues and challenges will inevitably arise if the outward and inward are incompatible and not in harmony. In this situation, a process of preaching can be transformed into a process of prayer, which is seen as wrong, perverted, misguided and even lost. The slogan “Hold on to Q&S” or “Return to Q&S” is widely used, both internally and externally. This article aims to address this issue from the background and developmental perspective; views of the Qur'an and the Sunnah; issues and challenges with various polemics that have emerged among the khawwas and ‘awwam. The findings show that the use of slogans has several objectives, for the Mu’minin people, something ideal needs to be realized in life. For Muslims, something is ideal and everyone should try to realize it, while for Munafiqin, opportunist and hypocrites, it is something that can be used for two-pronged purposes. Keywords: Slogan Q&S, Islamic thought